RESPON KEPALA KELUARGA TERHADAP PERKAWINAN USIA DINI (Di Desa Bantayan Kecamatan Batu Hampar Kabupaten Rokan Hilir) - Hani Wulandari; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine teh response of family heads to early marriage in the village of Bantayan, Batu Hampar District, Rokan Hilir Regency. The formulation of the problem in this study was to see how the family heads responded to early marriage couples in Bantayan Village. This study uses descriptive research with a quantitative approach. This data collection technique uses observation and questionnaires, taking samples in this study using simple random sampling. Thye results and discussion of this study is the massive public response to early marriage, the village of Bantayan, Batu Hampar Sudistrict, Rokan Hilir Regency, which means the community’s response to early marriage the Bantayan District of Batu Hampar, Rokan Hilir Regency is good.  Keywords: response, head of family, early marriage